Influence of the gas composition on the geometry of laser-welded joints in duplex stainless steel - Bauer, Branko (Materiali in tehnologije, 2011)
Shielding gases, i.e., argon or an argon-nitrogen mixture, are normally used during the laser-beam welding of duplex stainless steel. Helium is also often added to the argon. The effect of the type of shielding gas - argon, nitrogen, helium and their mixtures - on the geometrical characteristics of laser-welded joints of the duplex steel W.Nr. 1.4462 was studied. The welding was carried out according to the experimental model with mixtures. The effect of the welding speed and the gas flow rate were additionally explored using a factorial experiment. The obtained data were statistically processed and mathematical modeling, applying the method of response surfaces, was carried out. The analysis revealed that the impact of the shielding gas mixtures on the geometrical characteristics of the joint is significant. The effect of the gas flow rate on the geometrical characteristics was registered, while the effect of the heat input is the most significant. Special cubic, quadratic and reduced quadratic models, depicting the effects of the shielding gases on the geometrical characteristics of the welded joint, were obtained.
Keywords: lasersko varjenje; dupleksno jeklo; zaščitni plini; zvari